Usability of Spatial Analysis for Improving the Functioning of the Blood Donation System in Poland - Twaróg, Sebastian; Ojrzyńska, Anna (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
The paper aims at understanding how blood resources are formed at the entrance to the blood donation in the spatial and age section and formulating on the basis of this assessment recommendations that help improve the health safety of the State in the area of self‑sufficiency of blood supplies. The success of the functioning of blood donation primarily depends on the resource management of blood and its components that seeks to equate supply and demand for blood and its components at any time. Such a situation is possible when a sufficient number of blood donors are available. The research employed a shift‑share analysis that is used to study structural changes in economic and social phenomena that may occur in a geographical area within a specified period of time. To account for the fact that each province does not exist as a separate geographic area but depends on its spatial interactions with neighbouring areas, the study also used a spatial shift‑share analysis. The results will be used to assess the dynamics of changes in the number of blood donors, resulting from the age structure of blood donors in a particular province (a structural effect) and from changes in the internal situation of the competitiveness of a given area (a geographic effect). Knowledge concerning the nature of these changes can be helpful in developing specific tools that would encourage donors (including the potential ones) to donate blood.